Airframe noise measurements on JAXA Jet Flying Test Bed "Hisho" using a phased microphone array. Issue 4 (July 2017) - Takaishi, Takehisa; Ura, Hiroki; Nagai, Kenichiro; Yokokawa, Yuzuru; Murayama, Mitsuhiro; Ito, Yasushi; Sakai, Ryotaro; Shoji, Hirokazu; Yamamoto, Kazuomi
In 2015, the Japan Aerospace Exploration Agency launched theF light demonstration ofQU iet technology toR educe nO ise fromH igh-lift configurations project to verify by flight demonstration the feasibility of practical noise-reducing aircraft modification concepts. In order to serve as a baseline for comparison before modification, airframe noise sources of the JAXA Jet Flying Test Bed "Hisho" were measured with a 30 m diameter array of 195 microphones mounted on a wooden platform built temporary beside the runway of Noto Satoyama Airport in Japan. A classical Delay and Sum in the time domain beamforming algorithm was adapted for the present study, with weight factors introduced to improve the low-frequency resolution and autocorrelations eliminated to suppress wind noise at high frequencies. In the landing configuration at idle thrust, the main landing gear, nose landing gear, and side edges of the six extended flap panels were found to be the dominant "Hisho" airframe noise sources. Deconvolution by the DAMAS and CLEAN-SC algorithms provided clearer positions of these sound sources at low frequencies. Integration of acoustical maps agreed well with the sound pressure level measured by a microphone placed at the center of the microphone array and gave detailed information about the contribution of each noise source.